Ectopic gall bladder An interesting case report - Reza, Sharmin; Nasreen, Faria; Quddus, Sharmin; Mandal, Tapati; Hussain, Ferdous Ara (Bangladesh Journal of Nuclear Medicine, 2016)
Ectopic gall bladder is a rare entity. It can often be misdiagnosed causing diagnostic dilemma leading to various complications. Ultrasonography is the most common investigation for evaluating gall bladder pathologies. However, the confirmation of ectopic gallbladder is not easily possible by this method. On the other hand, hepatobiliary scan (HIDA scan) plays an important role in evaluating the presence and position of ectopic gallbladder. Here we present a case of sonographically suspected ectopic gallbladder confirmed by hepatobiliary scan highlighting the importance of HIDA scan in ectopic gallbladder. Bangladesh J. Nuclear Med. 17(2): 156-158, July 2014